Genus Aristida in Western Rajasthan - Kanodia, K. C.; Nanda, P. C. (Indian Forester, 1968)
The genus Aristida is one of the first grasses which provide forage to animals at the onset of monsoon. A careful scrutiny of the herbarium material coupled with critical field studies have proved that seven species and two varieties occur in this region. Aristida royleana Trin. Et Rupr. and A.juniculata var. mallica (Edgew.) Henr. have been reported as new records for the Rajasthan State. Their distinguishing characters have also been analytically illustrated. Aristida pungens Desf. And A. plumosa Linn., which are valuable fodder grasses of other desert regions, have been recommended for trials in Western Rajasthan.